2009
DOI: 10.1002/cpp.640
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐treatment predictors and in‐treatment factors associated with change in avoidant and dependent personality disorder traits among patients with social phobia

Abstract: We examined changes in avoidant and dependent personality disorder dimensions, and pre-treatment and in-treatment factors associated with such changes in 77 patients, randomized to medication-free residential cognitive (CT) or residential interpersonal therapy for social phobia. Personality disorders and personality dimensions according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) were assessed at pre-treatment and at one-year post-treatment. Both treatments were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Therefore, it is important to identify and treat personality traits early (Tyrer, Seivewright, & Johnson, 2004;Skodol, Geier, Grant, & Hasin, 2014). Both short-term group psychotherapy and cognitive behavioral therapy have been shown to be efficacious in the treatment of dependent personality in adults (Jensen, Mortensen, & Lotz, 2008;Borge et al, 2010). One study has shown that a brief parent intervention programme for preschool children with an anxiety disorder and behavioral inhibition led to reduced anxiety and behavioral inhibition in these children (Kennedy, Rapee, & Edwards 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to identify and treat personality traits early (Tyrer, Seivewright, & Johnson, 2004;Skodol, Geier, Grant, & Hasin, 2014). Both short-term group psychotherapy and cognitive behavioral therapy have been shown to be efficacious in the treatment of dependent personality in adults (Jensen, Mortensen, & Lotz, 2008;Borge et al, 2010). One study has shown that a brief parent intervention programme for preschool children with an anxiety disorder and behavioral inhibition led to reduced anxiety and behavioral inhibition in these children (Kennedy, Rapee, & Edwards 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A similar section was developed for assessing tics, Tourette disorder and other tic disorders. The structured clinical interview for DSM-IV (Spitzer, Williams, Gibbon, & First, 1992) was used for assessing other major Axis I diagnoses and the 'Kiddie' or K-SADS was used to classify Sep-AD (Chambers et al, 1985). A semistructured assessment protocol was used for additional diagnoses of interest in OCD (pathologic nail biting, pathological skin picking, trichotillomania, gambling, kleptomania and pyromania).…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…Researchers have reported small positive effects (e.g., d = 0.19) in clinical trials of time-limited (Alexander & Abeles, 1968) and long-term (Blatt, 1992, Blatt & Ford, 1994 psychodynamic therapies for dependent clients with comorbid diagnoses. To the author's knowledge, six studies have explored the effectiveness of cognitive-behavioral treatments for dependency, with three reporting significant results (Borge et al, 2010;Nelson-Gray et al, 1996;Rathus et al, 1995) and three reporting nonsignificant findings (Black et al, 1996;Moore & Blackburn, 1996;Rector et al, 2000). Bornstein (2004) summarizes the effectiveness of current treatments for dependency as "modest" (p. 294).…”
Section: Interpersonal Dependencymentioning
confidence: 99%
“…Although patients with cluster A (odd or eccentric) or cluster B (dramatic) personality disorders may suffer from social phobia and may be even more difficult to treat (Dimaggio, Attin a, Popolo, & Salvatore, 2012), the opposite link is less obvious (Hummelen, Wilberg, Pedersen, & Karterud, 2007). Overall, social phobia is associated with the anxious cluster C personality disorders (avoidant, dependent and obsessive compulsive clusters), with the strongest link to avoidant personality disorder (Borge et al, 2010;Hummelen et al, 2007;Sanderson, Wetzler, Beck, & Betz, 1994;Svrakic et al, 2002;Tyrer, Gunderson, Lyons, & Tohen, 1997).…”
mentioning
confidence: 99%